Enhancing LMS Effectiveness in Language Centers: A Case Study of V-Hub at VUS Vietnam - Nguyen, Duy Khang; Pham, Ngoc Chau (AsiaCALL Online Journal, 2025)
This mixed-methods study investigates the effectiveness of V-Hub, a Learning Management System (LMS) implemented at VUS, a prominent language center in Vietnam, focusing on homework completion rates and teacher strategies. A survey of 27 teachers and in-depth interviews with six teachers reveal that while V-Hub's user-friendly interface and learning content is positively perceived, technical limitations, such as device compatibility issues and the absence of answer explanations, hinder its full potential. Teachers employ various strategies to motivate and support students in using V-Hub, including rewards, personalized guidance, and clear communication. The study highlights the crucial role of teachers in effectively integrating LMS into language teaching and underscores the need for platform enhancements and comprehensive teacher training to maximize the benefits of technology-mediated language learning. Future research directions include exploring student perspectives, investigating the impact of specific LMS features on learning outcomes, and examining the potential for LMS materials to replace traditional textbooks.
Keywords: Technology-mediated language learning, online homework, LMS design, student engagement, teacher training